2. Efektivitas Collaborative Governance Dalam Kebijakan Penanganan Stunting - Ahmad Sururi; Rahmi Mulyasih; Rahmi Winangsih (Badan Perencanaan Pembangunan, Riset dan Inovasi Daerah Kabupaten Sragen, 2025)
The purpose of this study is to analyze the effectiveness of collaborative governance in stunting management policies in Serang Regency. This study uses a qualitative descriptive approach. The selection of the research location was carried out in Mongpok Village, Cikeusal District, Serang Regency. Data collection techniques through observation and interviews with 12 (twelve) informants. Data were analyzed using systematic qualitative data analysis, namely through the stages and processes of data classification (data coding), labeling, and category compilation. The results of the study indicate that the effectiveness of collaborative governance in stunting management policies in Mongpok Village, Serang Regency is quite effective based on four approaches, namely optimizing needs and use of resources, results achieved, collaboration processes and stakeholder satisfaction. The findings of the study indicate the importance of active commitment and responsibility on local actors such as village heads, community and religious leaders in overcoming various problems of stunting management that occur in the community and at the same time encouraging the important role of religious and community leaders to actively participate in every socialization activity and invite the entire community to behave cleanly and healthily in an effort to succeed in stunting management policies